How to Create Brand Awareness to Increase Purchase Decisions: Case study of Piaggio Vespa Matic in Bekasi, Indonesia - Dwi Entia; Joseph MJ Renwarin; M Richo Rianto; Matdio Siahaan; Djuni Thamrin; Annisa D Ambarwati; Silvia A Chairunnisah; Husni F Ramadhan; Hendy Tannady (STIKes Ibnu Sina Ajibarang, 2024)
Bekasi is the second city with the highest number of drivers in Indonesia. Honda is one of the automotive companies that dominates Indonesia. Piaggio Vespa Matic is a tertiary product which is not only offered to fulfill needs but is included in tertiary products. Researchers want to see how proud Vespa Matic users are. The purpose of this research is to determine the influence of Brand Image and Brand Awareness on purchasing decisions for Piaggio Vespa Automatic in Bekasi, Indonesia. Research using quantitative methods uses purposive sampling as sample determination with a total of 180 respondents and the Smart PLS technique. The research results show that Brand Awareness and Brand Image have an influence on the decision of Piaggio Vespa Matic buyers in Bekasi. Therefore, this research has an interesting topic that can explain what factors can influence the decision to purchase the legendary scooter, namely the Piaggio Vespa Matic in Bekasi, West Java, Indonesia.